Lung transplantation for pulmonary sarcoidosis - Meyer, Keith C. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2019)
Although relatively few patients with pulmonary sarcoidosis develop advanced disease that progresses to respiratory insufficiency despite receiving best practice pharmacologic interventions, lung transplantation may be the only therapeutic option for such patients to both prolong survival and provide improved quality of life. Lung transplant can be successfully performed for patients with end-stage pulmonary sarcoidosis, and post-transplant survival is similar to that for other transplant indications such as idiopathic pulmonary fibrosis. However, appropriate timing of referral, comprehensive assessment of potential candidates for lung transplant, placement of patients on the lung transplant waiting list when within the transplant window as appropriate, choosing the best procedure (bilateral versus single lung transplant), and optimal peri-operative and post-transplant management are key to successful lung transplant outcomes for patients with sarcoidosis.